Contention-sensitive data structures and algorithms - Taubenfeld, Gadi (Theoretical computer science, 2017)
A contention-sensitive data structure is a concurrent data structure in which the overhead introduced by locking is eliminated in common cases, when there is no contention, or when processes with non-interfering operations access it concurrently. When a process invokes an operation on a contention-sensitive data structure, in the absence of contention or interference, the process must be able to complete its operation in a small number of steps and without using locks. Using locks is permitted only when there is interference. We formally define the notion of contention-sensitive data structures, propose four general transformations that facilitate devising such data structures, and illustrate the benefits of the approach by implementing a contention-sensitive consensus algorithm, a contention-sensitive double-ended queue data structure, and a contention-sensitive election algorithm.